(untitled) (Jurnal Teknologi Industri Pertanian, 2026)
Pineapple chips are a snack from sliced pineapples that are deep-fried and contain permitted food additives. The production activities of pineapple chip agroindustry have the potential to cause environmental impacts. Therefore, a comprehensive assessment of emissions generated throughout the life cycle of pineapple chip production is necessary using the Life Cycle Assessment (LCA) approach. This study aims to calculate the environmental emission potentials from the life cycle of pineapple chips, covering stages from cultivation to distribution. The research stages include goal and scope definition, inventory analysis using the mass balance method, impact assessment using the Open LCA software, and interpretation. The life cycle of the pineapple chips begins with land preparation for cultivation, including nursery, maintenance, and harvesting. The harvested pineapples are then transported to the processing facility, where they are transformed into packaged pineapple chips and distributed to souvenir centres. The results of the environmental impact assessment for a functional unit of 100 grams of pineapple chips show emissions of 7.04E-01 kg CO₂-eq for global warming potential (GWP), 2.29E-03 kg SO₂-eq for acidification potential (AP), 1.42E-02 kg PO₄-eq for eutrophication potential (EP), and 1.08E-08 kg CFC-11 eq for ozone depletion potential (ODP). The life cycle analysis reveals that the production stage is the main contributor to emissions, with eutrophication potential (EP) identified as the hotspot. To reduce the environmental burden, three improvement scenarios are proposed: substitution of chemical fertilizers with compost, conversion of gasoline to gas fuel, and replacement of palm oil with coconut oil. Keywords: environmental emissions, life cycle assessment, pineapple chips